Best Paper Award - Gregoriades, Andreas (My University, 2026)
Best paper award for the paper with title : An Intelligent System to Enhance Traffic Safety Analysis Andreas Gregoriades, Kyriacos Mouskos, Neville Parker, Ismini Hadjilambrou, Natalia Ruiz-Juri, Aneesh Krishna at the International Conference on Performance, Safety and Robustness in Complex Systems and Applications
Keywords: Arts and entertainment